Answer:
Step-by-step explanation:
Transformed of the function has been given as,
f(x) = ![\sqrt{(2x+6)}+3](https://tex.z-dn.net/?f=%5Csqrt%7B%282x%2B6%29%7D%2B3)
= ![\sqrt{2}(\sqrt{x+3})+3](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D%28%5Csqrt%7Bx%2B3%7D%29%2B3)
Parent function of this transformed function = ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
Vertical stretch = By a factor of ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Horizontal shift = 3 units to the left
Vertical shift = 3 units up
Now we can summarize these transformations as,
1). Parent function g(x) =
has been vertically stretched by a factor of ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
2). Followed by the translations of 3 units left and 3 units up.